Antinociceptive and Anti-Inflammatory Activities of Bridelia retusa Methanolic Fruit Extract in Experimental Animals. (17th November 2014) - Kumar, Tekeshwar; Jain, Vishal
Abstract : Antinociceptive and anti-inflammatory potentials of methanolic extract of Bridelia retusa fruit (BRME) were evaluated against different animal models in rodents. Antinociceptive effects of BRME were assessed in mice using the acetic acid-induced writhing and formalin test. Anti-inflammatory effects of BRME in three different doses, namely, 100, 200, and 400 mg/kg, were evaluated by utilizing different animal models representing various changes associated with inflammation, namely, carrageenan-induced paw oedema, histamine and serotonin-induced paw oedema, arachidonic acid-induced paw oedema, formalin-induced paw oedema, TPA-induced ear oedema, acetic acid-induced vascular permeability, total WBC count in paw fluid, and myeloperoxidase assay. Also BRME was phytochemically evaluated using chromatographic method. The BRME did not exhibit any signs of toxicity up to a dose of 2000 mg/kg. The extract showed statistical significant inhibition of induced nociception and inflammation in dose dependent manner. The higher dose of extract significantly inhibited pain and inflammation against control (P < 0.001 ). HPLC results revealed the presence of gallic acid and ellagic acid as phytoconstituents in BRME and it was proven as anti-inflammatory agents. The present study scientifically demonstrated the antinociceptive and anti-inflammatory potential of fruit of B. retusa methanolic extract. These effects may be attributed to the presence of polyphenolic phytoconstituents in the extract.